The case for taking a life-cycle perspective: Inequality, redistribution, and tax and benefit reforms - Barra Roantree; Jonathan Shaw (Institute for Fiscal Studies (IFS), 2014)
Most analysis of the impact of taxes and benefits on households is cross-sectional, with individuals classified as rich or poor, and gains and losses calculated, using a single snapshot of data. In this report, we argue the case for taking a longer-run perspective. In particular, we show that income and circumstances over longer horizons (such as several years) are likely to form a better basis for measuring living standards. We then demonstrate how common measures of inequality and redistribution, and distributional analyses of tax and benefit reforms, are affected by taking a longer-run perspective. Results from the two perspectives may look quite different from each other and, as a result, we could end up with contrasting impressions of the extent to which the tax and benefit system redistributes from rich to poor.
Keywords: 330